2014
DOI: 10.1186/s12917-014-0261-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the contributions of Hp-MMP 9 to the serum acute phase protein response of lipopolysaccharide challenged calves

Abstract: BackgroundBovine respiratory disease (BRD) is a costly feature of modern cattle production. Early and accurate detection of BRD may prove useful in the successful management of this disease. The primary objective of the study was to define the time course of covalent complexes of neutrophil, haptoglobin (Hp) and matrix metalloproteinase 9 (Hp-MMP 9) in serum after intravenous lipopolysaccharide (LPS) in comparison to traditional markers. Our hypothesis was that serum concentrations of neutrophil Hp-MMP 9 provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Thus, increased concentration and activity of gelatinases (MMP2 and MM9) were detected in lung lesion of calves with experimentally induced M. haemolytica pneumonia [4] and in tracheobronchial lavage fl uid of calves with concurrent infections of P. multocida and M. bovirhinis [49]. Hinds et al [30] using intravenous application of E. coli lipopolysaccharide as a model for acute phase protein responses showed that covalent MMP-9 haptoglobin complex (Hp-MMP-9) was detected in the serum before and declined more rapidly than other acute phase proteins, and assumed that Hp-MMP9 complex can be early and accurate markers of calf respiratory diseases. The serum level of Hp-MMP9 complex was confi rmed as a reliable biomarker of acute lung infl ammation in calves experimentally infected with M. haemolytica [46].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, increased concentration and activity of gelatinases (MMP2 and MM9) were detected in lung lesion of calves with experimentally induced M. haemolytica pneumonia [4] and in tracheobronchial lavage fl uid of calves with concurrent infections of P. multocida and M. bovirhinis [49]. Hinds et al [30] using intravenous application of E. coli lipopolysaccharide as a model for acute phase protein responses showed that covalent MMP-9 haptoglobin complex (Hp-MMP-9) was detected in the serum before and declined more rapidly than other acute phase proteins, and assumed that Hp-MMP9 complex can be early and accurate markers of calf respiratory diseases. The serum level of Hp-MMP9 complex was confi rmed as a reliable biomarker of acute lung infl ammation in calves experimentally infected with M. haemolytica [46].…”
Section: Discussionmentioning
confidence: 96%
“…Back in 1982 Yates [29] pointed out that in different cases of calf bronchopneumonia the leukocyte counts could vary from leucocytosis to leukopenia. We believe that these variations are a result of 1) multifactorial aetiology of the disease, 2) potent immunomodulatory effects of microbiological causative agents [1] and 3) time-dependent fl uctuation in the number of leukocytes in peripheral blood after disease induction [30]. All of these factors must be taken into consideration before declaring increased peripheral blood leukocyte count as a suitable biomarker of calf bronchopneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies aimed to evaluate time courses of SAA and other APPs, serum SAA increased in systemic inflammatory model cattle that endotoxin (ETX) challenged [ 4 , 12 , 28 ]. However, to the best of our knowledge, no studies have investigated sequential changes in mRNA expression of SAA isoform genes in ETX challenge model cattle.…”
mentioning
confidence: 99%
“…SN activation is accompanied by the intensification of metabolic processes (respiratory explosion) and the secretion of large amount of antibacterial substances differing in chemical nature [15][16][17]. Such stereotyped reaction occurs to metabolites of microbial origin, for example, lipopolysaccharides (LPS's) of gram-negative bacteria [18], as well as to hormones, blood and tissue cell mediators, and various kinds of radiation [19][20][21][22].…”
mentioning
confidence: 99%